Chemical investigation of the volatile oil from the leaves of Rosmarinus officinalis - Pacia, Maria Inez G.; Concepcion. Adoracion B.; Cruz, Ileana R. (Manila College of Pharmacy, University of the Philippines, 1985)
The air-dried leaves of Rosmarinus officinalis Linne yielded 1-2% of volatile oil. The volatile oil was obtained by steam distillation. The volatile oil, rosmarin contains d-pinene, cineol, borneol and camphene. The volatile was analyzed by thin later chromatography using iodine and the vanillin sulfuric acid as developers.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, October 1985.
Keywords: Rosemary; Essences and essential oils; Romero